Endometrioid Tubal Intraepithelial Neoplasia (E-TIN) of the Fallopian Tube: A Case Series. (November 2020) - Hecht, Jonathan L.; Lin, Douglas I.; Garrett, Leslie
Abstract : Although serous tubal intraepithelial carcinoma has been well described in the distal fallopian tube as precancers of pelvic high-grade serous carcinoma, endometrioid precancers have drawn less attention. Recently, endometrioid precursor lesions have been identified and reported to have a specific immunophenotype (PAX2−, ALDH1+, diffuse nuclear beta-catenin), as well as an association with both uterine and ovarian endometrioid carcinomas. These have been referred to as endometrioid (or type II) secretory cell outgrowths. A subset of endometrioid secretory cell outgrowths show architectural complexity resembling hyperplasia of the endometrium and have been referred to as endometrioid tubal intraepithelial neoplasia. We report 4 cases of endometrioid tubal intraepithelial neoplasia with clinical correlation and morphologic differential diagnosis.